FERTILITAS DAN DAYA TETAS TELUR HASIL PERSILANGAN ANTARA PUYUH ASAL BENGKULU, PADANG DAN YOGYAKARTA - Desia Kaharuddin; Kususiyah Kususiyah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
An experiment was carried out to examine the effect of sire and dam on fertility and hatchability of eggs from crossbreeding among Bengkulu (B), Padang (P) and Yogyakarta (Y) quails. Treatments, crosses of BB, PP, YY, BP, BY, PB, PY, YB, and YP, were arranged in a Completely Randomized Design with five replications. The result of this experiment showed that the fertility of sire and dam of Bengkulu pure breed (BB, 77%) were significantly lower than Padang pure breed (PP) and other crossbreeds (BP, PB, PY, YP, BY and YB) but being not significantly different than fertility of Yogyakarta pure breed (YY). Hatchability of BB (71.12%) was not significantly different with hatchability of YY, BY and BP, but it was significantly lower than another croosbreed (PY, YP, YB and PB) and PP. The higher egg fertility and hatchability of crossbreed between Bengkulu quails and those of sire and dam from Yogyakarta or Padang as compared with those of Bengkulu quails pure breed shows potential for larger scales quail egg production. However, further researches need to be conducted to improve egg productivity of the crossbreeds.